Synthetic Nanoparticles That Promote Tumor Necrosis Factor Receptor 2 Expressing Regulatory T Cells in the Lung and Resistance to Allergic Airways Inflammation - Mohamud, Rohimah; LeMasurier, Jeanne S.; Boer, Jennifer C.; Sieow, Je Lin; Rolland, Jennifer M.; O’Hehir, Robyn E.; Hardy, Charles L.; Plebanski, Magdalena (Frontiers in Immunology, 2017)
Synthetic glycine coated 50 nm polystyrene nanoparticles (PS50G), unlike ambient nanoparticles, do not promote pulmonary inflammation, but instead render lungs resistant to the development of allergic airway inflammation (AAI). In this study we show that PS50G modulate the frequency and phenotype of regulatory T cells (Treg) in the lung, specifically increasing the proportion of tumour necrosis factor 2 (TNFR2) expressing Treg. Mice pre-exposed to PS50G, which were sensitised and then challenged with an allergen a month later, preferentially expanded TNFR2+Foxp3+ Treg, which further expressed enhanced levels of latency associated peptide (LAP) and cytotoxic T-lymphocyte associated molecule-4 (CTLA-4). Moreover, PS50G CD103+ dendritic cell (DC) activation in the lung was associated with the proliferative expansion of TNFR2+Foxp3+ Treg. These findings provide the first evidence that engineered nanoparticles can promote the selective expansion of maximally suppressing TNFR2+Foxp3+ Treg, and further suggest a novel mechanism by which nanoparticles may promote healthy lung homeostasis.